COLOR VISION DEFECT AND TOOTH SHADE SELECTION AMONG NIGERIAN DENTAL PRACTITIONERS - Bamise, Cornelius Tokunbo; Esan, Temitope Ayodeji; Akeredolu, Patricia Adetokunbo; Oluwatoyin, Onakpoya; Oziegbe, Elizabeth Obhioneh (Archives of Oral Research, 2007)
OBJECTIVES: The aim of this work is to assess the prevalence of color defect and the mode of tooth shade selection among dental practioners. MATERIAL AND METHODS: Two hundred self administered questionnaires were sent to all the dentists in the six dental schools in Nigeria. The color vision status of the respondents was assessed using Isihara test. The investigators were calibrated for examining the numbers in the plates by comparing the results of Isihara test administered to them and were adjudged not to be color blind. Data was analyzed using SPSS version 11. Analysis used included frequencies cross tabulation, chi-square analysis and Fisher’s exact tests. RESULTS: The prevalence of color blindness among Nigerian dentists working in teaching hospitals was found to be 6.3%. The prevalence was higher in males (8.4%) than in the females (3.9%) giving a male female ratio of 2.2:1. Color vision defect was highest among Pedodontists (33.3%), followed by Oral surgeon (8.3%) and general dental practice (6.5%). None in Conservative dentistry and Prosthodontics have color vision defect. Majority of those with color vision defect usually select color with concurrence from other dentist. CONCLUSION: The prevalence of color defect among dentists in Nigeria is high compared to other studies. Dentists should be screened for color vision defect before they choose their specialty.